2022
DOI: 10.7554/elife.79491
|View full text |Cite
|
Sign up to set email alerts
|

The proportion of randomized controlled trials that inform clinical practice

Abstract: Prior studies suggest that clinical trials are often hampered by problems in design, conduct and reporting that limit their uptake in clinical practice. We have described 'informativeness' as the ability of a trial to guide clinical, policy or research decisions. Little is known about the proportion of initiated trials that inform clinical practice. We created a cohort of randomized interventional clinical trials in three disease areas (ischemic heart disease, diabetes mellitus and lung cancer), that were init… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…Besides these updates, further transparency practices may be integrated into the dashboard in the future, e.g., dissemination of results as preprints, the use of self-archiving to broaden access to results [ 51 ], adherence to reporting guidelines [ 3 ], or data sharing [ 52 ]. Beyond transparency, other potential metrics could reflect the number of discontinued trials [ 53 ] or the proportion of trials that inform clinical practice [ 54 ]. The development of such metrics should acknowledge the availability of standards and infrastructure pertaining to the underlying practices [ 23 ] and differences between study types and disciplines [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides these updates, further transparency practices may be integrated into the dashboard in the future, e.g., dissemination of results as preprints, the use of self-archiving to broaden access to results [ 51 ], adherence to reporting guidelines [ 3 ], or data sharing [ 52 ]. Beyond transparency, other potential metrics could reflect the number of discontinued trials [ 53 ] or the proportion of trials that inform clinical practice [ 54 ]. The development of such metrics should acknowledge the availability of standards and infrastructure pertaining to the underlying practices [ 23 ] and differences between study types and disciplines [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 14. Process Area 10, Reliability and quality 4 Terms included: Reliability Growth: "Reliability growth is defined as the positive improvement in a reliability metric or parameter of a product (e.g., a system) over a period of time due to changes in the product's design and/or the manufacturing process." [37] Quality Control: "While reliability is concerned with the performance of a product over its lifetime, quality control is concerned with performance of a product at a point in time."…”
Section: Ml1 Initialmentioning
confidence: 99%
“…2 dedicated scientific design review. This may account for the large difference in informativeness between industry and non-industry clinical trials (CT) found recently [4].…”
mentioning
confidence: 99%
“…One study of 125 diabetes, ischaemic heart disease, and lung cancer trials reported that only 26% fulfilled the authors’ four criteria of informativeness (clinical question, design, feasibility, reporting). 10 Another similar study of 347 gynecology and obstetrics trials reported that only 10% fulfilled minimum half of the authors’ eight prespecified ‘usefulness’ criteria (clinical question, preceding systematic review, power, pragmatic, patient oriented, financially worth it, transparency). 11 One main reason for this lack of ‘informativeness’ may be that it is not a priority during medical, graduate, and postgraduate training to learn about proper conduct of clinical trials, and access to freely available quality educational material may also be sparse.…”
Section: Introductionmentioning
confidence: 99%